KINERJA KOPERASI UNIT DESA (KUD) WENANG DITINJAU DARI BALANCED SCORECARD - Romaida ., Br. Sagala; Lyndon R.J. Pangemanan; Yolanda P. I. Rori (Sam Ratulangi University, 2016)
Research aims to determine how the performances of Koperasi Unit Desa (KUD) Wenang in Manado City evaluated from Balanced Scorecard are financial perspective, customer perspective, internal business processes perspective, and learning and growth perspective. Research carried out in July until September 2016. Data used is quantitative and qualitative with data source are primary and secondary data obtained from KUD with a total sample of 96 member respondents, 96 non member respondents with accidental sampling (technique) and 25 employees with sensus. Therefore the total samples are 217 respondents. Data analysis that used Balanced Scorecard method and criteria for the balance of the balanced scorecard that analyzes of financial perspective, customer perspective, internal business processes perspective, and learning and growth perspective while the balance is using a rating scale criteria. Research result showed that the performance of Koperasi Unit Desa (KUD) Wenang reviews from the Balanced Scorecard is internal business process perspective are considered good and satisfying customer perspective rated good and satisfying, as well as financial perspective judges not good enough with an overall score is 0,4 or equal to pretty good.